Workplace violence in emergency departments: The health professionals and security personnel alliance. (27th August 2020) - Ramacciati, Nicola; Giusti, Gian Domenico
Abstract: Violence in the health sector is a widespread worldwide phenomenon. Emergency nurses and emergency physicians are among the most exposed. In violent incidents, security personnel also play an important role. Wand and colleagues on Emergency Medicine Australasia have tried to give voice to the opinions and experiences of security personnel in responding to aggression and behavioural problems. Sharing some data from our 2016 Italian National Survey on Violence towards Emergency Nurses, further elements are provided on this issue. The different perspectives of healthcare professionals and security personnel can converge in an alliance to counteract violence in the ED.